Sunset express : an Elvis Cole novel - Crais, Robert (New York : Hyperion, 1997)
When a wealthy restaurateur is accused of murdering his wife in Los Angeles, wisecracking private eye Elvis Cole is hired to prove that the evidence was corrupted and becomes suspicious about the defense attorney's motivations.
National College of Business and Arts
Keywords: Murder -- Investigation -- Fiction; Detective and mystery fiction